Answer:
Since g(x) = f(2x), this means we substitute 2x in place of x for f(x):
g(x) = f(2x) = (2x)² = 4x²
Graphing this, the parabola is not moved from the parent graph f(x) = x², but the graph is compressed horizontally by a factor of 4.Step-by-step explanation:
The correct answer is: [B]: " 25 a²⁵ b²⁵ " .
_________________________________________________________
<span>Explanation:
_________________________________________________________
Given the expression:
_________________________________________________________
</span>→ " (−5a⁵b⁵)² (a³b³)⁵ " ; Simplify.
_________________________________________________________
Let us being by examining:
______________________________________
→ "(−5a⁵b⁵)² " .
→ "(−5a⁵b⁵)² = (-5)² * (a⁵)² * (b⁵)² = (-5)(-5) * a⁽⁵ˣ²⁾ * b⁽⁵ˣ²⁾ = 25a⁽¹⁰⁾b⁽¹⁰⁾ ;
{Note the following properties of exponents:
(xy)ⁿ = xⁿ * yⁿ ;
(xᵃ)ᵇ = x⁽ᵃ * ᵇ) ;
(xᵃ) * (xᵇ) = x⁽ᵃ ⁺ ᵇ⁾ .}.
______________________________________
Then, we examine:
______________________________________
→ "(a³b³)⁵ " .
→ "(a³b³)⁵ = a⁽³ˣ⁵⁾b⁽³ˣ⁵⁾ = a⁽¹⁵⁾b⁽¹⁵⁾ .
______________________________________
So: " (−5a⁵b⁵)² (a³b³)⁵ = (-5)a⁽¹⁰⁾b⁽¹⁰⁾ * a⁽¹⁵⁾b⁽¹⁵⁾ " ;
________________________________________
Now, we simplify:
→ " 25a⁽¹⁰⁾b⁽¹⁰⁾ * a⁽¹⁵⁾b⁽¹⁵⁾ " ;
→ " 25a⁽¹⁰⁾b⁽¹⁰⁾ * a⁽¹⁵⁾b⁽¹⁵⁾ ;
= 25a⁽¹⁰⁾ a⁽¹⁵⁾b⁽¹⁰⁾ b⁽¹⁵⁾ ;
= 25a⁽¹⁰ ⁺¹⁵⁾ b⁽¹⁰⁺¹⁵⁾ ;
= 25a⁽²⁵⁾ b⁽²⁵⁾ ;
_______________________________________________
→ which is: Answer choice: [B]: " 25 a²⁵ b²⁵ " .
______________________________________________
B becuase if you divide the rise over run you get 45 which is the correct answer.
hope this helps
-turtles12345
Answer:
yes
Step-by-step explanation:
Answer:
The answer is 49
Step-by-step explanation:
the square = 10×4= 40
The triangle = 6×3= 18 >> 18÷2 = 9ft
40+9= 49ft